Characteristics of Good Teacher Leadership: Viewed from Students’ Perspectives at Faculty of Language Education in Private University - Imansyah, Faiz Atha; Purwanti, Eko; Nizaratif , ekopurwanti@umy.ac.id; Fathi, Hawari Nadhal; Kusuma, Dimas Krisna Wijaya (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Teachers play a crucial role in education by imparting knowledge, fostering critical thinking, and creating positive learning environments. This study explores students' perceptions of successful teacher leadership and its influence on their learning experiences. Teacher leadership impacts student achievement and school enhancement through mentoring, cooperation, and creativity. Understanding students' perspectives on effective teacher leadership is vital for educators, administrators, and policymakers. While much research exists on teacher leadership in educational practice, there is a gap regarding student perceptions of teacher leadership characteristics. This study aims to fill that gap using a qualitative descriptive design with in-depth interviews of language education students. A qualitative approach was employed to gather rich, detailed data, with 6 participants selected from different language education programs to provide diverse insights into teacher leadership characteristics. The findings reveal that students identify the following characteristics of effective teacher leadership: 1) high dedication, 2) supportive teacher, 3) good communication skills, and 4) good empathy. These traits significantly contribute to successful teacher leadership in the classroom. This study is valuable for those seeking to understand the key characteristics of effective teacher leadership.